2015
DOI: 10.1186/s12906-015-0815-0
|View full text |Cite|
|
Sign up to set email alerts
|

Neuroprotective effect of Spirulina fusiform and amantadine in the 6-OHDA induced Parkinsonism in rats

Abstract: BackgroundMulti-factorial etiology exists in pathophysiology of neurodegenerative diseases. The imbalance of anti-oxidant enzymes and dopamine level leads to Parkinsonism. The objective of this study was to assess the protective effect of Spirulina fusiform alone and in combination with amantadine against Parkinsonism effect in 6-hydroxydopamine (6-OHDA) induced rat model.MethodsS. fusiform was administered in different groups (500 mg/kg, once daily and twice daily) and a combination of spirulina (500 mg/kg, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…34 Spirulina platensis has different roles, such as anti-inflammatory, anti-oxidative, neuroprotective, and hepatoprotective properties. 20,31,32,35 Because of its neuroprotective and antioxidant properties, the findings of the present study suggest that the application of Spirulina platensis as a natural food supplement is useful to prevention the cognitive-behavioral impairment induced by stress.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…34 Spirulina platensis has different roles, such as anti-inflammatory, anti-oxidative, neuroprotective, and hepatoprotective properties. 20,31,32,35 Because of its neuroprotective and antioxidant properties, the findings of the present study suggest that the application of Spirulina platensis as a natural food supplement is useful to prevention the cognitive-behavioral impairment induced by stress.…”
Section: Discussionmentioning
confidence: 76%
“…Rats randomly were distributed into 4 following groups (10 animals in each group). Control group: rats received only oral physiological saline using gavage tube; SP group: rats received 200 mg/kg SP per day for 15 days using gavage tube (PNDs 41-55); Stress group: rats exposed to 10 days restraint stress (PNDs [30][31][32][33][34][35][36][37][38][39][40] and Stress + SP group: rats exposed to stress and then received SP for 15 days (PNDs 41-55). Biochemical assessments began at the PND 61 after the termination of all intervention procedure.…”
Section: Experimental Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, amantadine can alleviate local inflammation in the brain tissue of animals with experimental Parkinson's disease. Specifically, amantadine 20 mg/kg exhibited antiradical activity by reducing the intensity of lipid peroxidation and increasing glutathione content in the substantia nigra of rats with 6-hydroxydopamine-induced Parkinson's disease [49]. This drug reduced lipopolysaccharide-and 1-methyl-4-phenylpyridinium ion (MPP+)-induced toxicity of dopamine neurons through 1) the inhibition of the release of microglial pro-inflammatory factors, 2) an increase in expression of neurotrophic factors such as GDNF from astroglia [50].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive Oxygen Species (ROS) play a vital role in the induction of neurodegeneration, and phycocyanin (C-PC) and phycocyanobilin show strong antioxidant activity, reduce ROS and help in protection from neurodegenerative conditions (Cervantes-Llanos et al, 2018; Pentón-Rol, Marín-Prida, & Falcón-Cama, 2018). Furthermore, it has been shown that dietary supplementation of Spirulina protects tyrosine hydroxylase positive neurons in an intra-striatal 6-OHDA lesion model of Parkinson's disease (Chattopadhyaya et al, 2015;Stramberg, Gemma, Vila, & Bickford, 2005). The available report demonstrated that microglia play a key role in generating neurodegenerative diseases and supplementation of Spirulina shows a neuroprotective effect by downregulating MHC II expression in microglia (Pabon et al, 2012).…”
Section: Cyanobacteria As a Neuroprotective Agentmentioning
confidence: 99%